2020
DOI: 10.1590/0102-33062019abb0381
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination and dormancy break in Eragrostis polytricha, a native Brazilian grass species with potential for recovery of degraded lands

Abstract: Ferruginous Rocky Outcrops have high levels of species richness and endemism, but have been threatened by several anthropic actions, especially mining. Eragrostis polytricha, a common grass species in the vegetation of these outcrops, has shown promising features for use in the recovery of mining areas. However, in order to fully understand the species' potential for such use, its requirements for germination, seed dormancy break and seedling development must be determined. Thus, we aimed to: (1) assess the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Dormancy among caryopses of native grass species has been previously reported (Ramos et al 2017(Ramos et al , 2019Saraiva et al 2020) and different cues, as smoke and heat shock (Ramos et al 2019) as well as KNO 3 and alternating temperatures (Carmona et al 1998;Saraiva et al 2020) were reported to improve their germination. Caryopses of G. doellii are dormant at harvest, but alternating temperature treatments, coupled or not with KNO 3 and light were shown to considerably improve germination (Carmona et al 1997).…”
Section: Resultsmentioning
confidence: 83%
“…Dormancy among caryopses of native grass species has been previously reported (Ramos et al 2017(Ramos et al , 2019Saraiva et al 2020) and different cues, as smoke and heat shock (Ramos et al 2019) as well as KNO 3 and alternating temperatures (Carmona et al 1998;Saraiva et al 2020) were reported to improve their germination. Caryopses of G. doellii are dormant at harvest, but alternating temperature treatments, coupled or not with KNO 3 and light were shown to considerably improve germination (Carmona et al 1997).…”
Section: Resultsmentioning
confidence: 83%
“…Osmopriming with chemical agents such as calcium nitrate and potassium nitrate stimulates seed germination by generating a water potential balance between the seeds and the solution via osmosis [8,9] . Pretreatment with potassium nitrate reduced dormancy and improved seed germination [10,11] . Gibberellic acid is a plant hormone that is essential for fruit plant growth and yield.…”
Section: Introductionmentioning
confidence: 99%